Exploring the Association between Fruit and Vegetable Consumption and Depression among a Saudi Adult Population: A Cross-Sectional Study - Fatimah Yousef; Buthaina Aljehany (International Journal of Food and Nutritional Health, 2026)
Research has increasingly highlighted the protective effects of fruit and vegetable consumption on depressive symptoms. However, less research has been examining the importance of relationships within the specific context of Saudi Arabia. Study aim to examine the relationship between fruit and vegetable intake and depression in Saudi adults. A total of 598 Saudi male and female adults residing in Jeddah,Saudi Arabia participated in this cross-sectional study. Participants completed an online questionnaire on fruits and vegetables consumption and Hospital Anxiety and Depression Scale to evaluate the presence and severity of depressive symptoms. Daily consumption of fruits and vegetables is not regular, being vegetables are less consumed than fruits. Regular and frequent fruit consumption is associated with lower depression severity. Individuals who consume fruits sometimes or less frequently are more likely to experience higher depression severity. Regular vegetable consumption is associated with lower depression severity, while fresh vegetable consumption is not significantly associated with depression severity. Unfrequent and insufficient intake of fruits and vegetables seems to be related to depression among Saudi adults. Promoting fruit and vegetable intake could help to mitigating depression symptoms and reduce the risk of developing depression. Further investigations are needed to demonstrate a potential causal relationship.